Fabrication of functionally graded Hydroxyapatite-Titanium by applying optimal sintering procedure and powder metallurgy - Shahrjerdi, Ali; Mustapha, Faizal; Bayat, Mehdi; Salit, Mohd Sapuan; Abang Abdul Majid, Dayang Laila (Academic Journals, 2011)
This paper demonstrates the functionally graded metal-ceramic composite fabricated via pressure-less sintering. The pure metallic and ceramic components are Titanium (Ti) and Hydroxyapatite (HA), which were located at the ends of a cylindrical specimen. FG samples are prepared with mixing ratios of 100:0, 75:25, 50:50, 25:75, 0:100. The cylindrical samples had a thickness of 6 mm in size and 20 mm radius. Samples are created by using carbon cylindrical die. The optimum thermal load mapping is obtained experimentally. The properties of all FGM products are characterized by shrinkage, optical microscope, scanning electron microscope (SEM), energy dispersive spectrometry (EDX) and hardness test. The grade of the FGM material is proven by results from all recorded measurements, as well as linearity of shrinkage. Result from optical micrograph and SEM indicate that the HA/Ti FG cylinder can be produced successfully by cold pressing with developed thermal mapping. Vicker’s hardness of HA/Ti is higher than that of pure microcrystalline Ti (metal) and reduces by decreasing the density of the layer of HA/Ti.